2001
DOI: 10.1021/tx0101191
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of 1-[3-(Aminomethyl)phenyl]-N-[3-fluoro-2‘- (methylsulfonyl)-[1,1‘-biphenyl]-4-yl]-3-(trifluoromethyl)- 1H-pyrazole-5-carboxamide (DPC 423) by Novel Metabolic Pathways. Characterization of Unusual Metabolites by Liquid Chromatography/Mass Spectrometry and NMR

Abstract: The in vitro and in vivo disposition of DPC 423 was investigated in mice, rats, dogs and humans and the metabolites characterized by LC/MS, LC/NMR and high field-NMR. The rodents produced several metabolites that included an aldehyde (M1), a carboxylic acid (M2), a benzyl alcohol (M3), glutamate conjugates (M4 and M5), an acyl glucuronide (M6) and its isomers; a carbamyl glucuronide (M7); a phenol (M8) and its glucuronide conjugate (M9), two glutathione adducts (M10 and M11), a sulfamate conjugate (M12), isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 25 publications
2
43
1
1
Order By: Relevance
“…Reports in the literature indicate that glycine and to a lesser extent glutamine are the most likely amino acids to be involved in the conjugation reactions of carboxylic acids (Hutt and Caldwell, 1990). It should also be added that recently the conjugation of xenobiotic amines with glutamate has also been reported (Mutlib et al, 2000;2002) In this study, quantitative analysis of the conjugates in human urine, serum, and CSF samples revealed that VPA-GLU was consistently the predominant amino acid conjugate compared with VPA-GLN, and VPA-GLY was a minor conjugate. The more extensive conjugation of VPA with glutamic acid than either glutamine or glycine is also an unprecedented observation for the human species.…”
Section: Discussionsupporting
confidence: 56%
“…Reports in the literature indicate that glycine and to a lesser extent glutamine are the most likely amino acids to be involved in the conjugation reactions of carboxylic acids (Hutt and Caldwell, 1990). It should also be added that recently the conjugation of xenobiotic amines with glutamate has also been reported (Mutlib et al, 2000;2002) In this study, quantitative analysis of the conjugates in human urine, serum, and CSF samples revealed that VPA-GLU was consistently the predominant amino acid conjugate compared with VPA-GLN, and VPA-GLY was a minor conjugate. The more extensive conjugation of VPA with glutamic acid than either glutamine or glycine is also an unprecedented observation for the human species.…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, several reports have appeared in the literature describing the metabolism of benzylamines and structural analogues and results have revealed that the benzylamine moiety was a metabolic soft spot. Oxidative deamination yielding the aldehyde was demonstrated to be a precursor of the corresponding acid metabolite, and the formation of the aldehyde intermediate and/or metabolite has been attributed to mitochondrial monoamine oxidase (MAO)-B. Acyl glucuronides, a carbamyl glucuronide, oxime, a glutathione adduct and N-acetylation were also reported (Timperio et al 2003;Mutlib et al 2001Mutlib et al , 2002aMutlib et al , 2002bMutlib et al , 2002cShaffer et al 2008). …”
Section: Discussionmentioning
confidence: 97%
“…Several methods have been described for the preparation and characterization of carbamoyl glucuronides using in vitro techniques, including both hepatocytes and hepatic microsomes, as well as chemical synthesis. Table 1 shows two examples, a piperazine BVT.2938 [46] and a benzylamine DPC 423 [47], where carbamate glucuronides were formed in hepatocytes from rats, monkeys, and humans. A procedure for forming carbamate glucuronide metabolites using liver microsomes fortified with UDPGA in the presence of CO 2 was developed for carvedilol [16] and has been used for the formation of several other carbamate glucuronides summarized in Table 1.…”
Section: Some Of the Compounds Shown Inmentioning
confidence: 99%